Citalopram induced nightmare in an elderly man: a case-report - Effat Davoudi-Monfared; Hamidreza Taghvaye Masoumi (Research Center for Rational Use of Drugs (RCRUD), 2017)
An 80-year-old man developed nightmares while using citalopram for mild depression. During the first two weeks of treatment with citalopram (10 mg daily), he didn't experience any adverse reactions. After two weeks, he developed nightmaresand vivid dreams that were repeated every night and awakened him in midnight. Although the signs of depression were relatively disappeared, the patient was anxious during the day due to nightmares and nocturnal awakenings. We, as pharmacists, consulted his family to decrease the dose to 10 mg every other day, and tell his physician as soon as possible. He decreased the doses and after two weeks the frequencyof nightmares was less. More follow-up revealed that the nightmares were totally disappeared one month after drug withdrawal. A Naranjo assessment score of 7 was obtained, showing a probable relationship between theadverse reaction and suspected drug.